Visualising the cost of quality investment using equity breakeven point. (2016) - Badiru, Adedeji B.
The fully-burdened cost of quality management programs must be viewed from a systems perspective with respect to the value impacted on the organisation. What appears to be cost-effective or cheap in the present scenario may proof to be costly (or even disastrous) in the long run of market share with respect to customer perception. This paper presents an application of the equity breakeven point technique for graphical analysis of quality investments. The mathematical derivation of the equity breakeven point indicates the time when the unpaid balance on a capital investment is equal to the cumulative equity in the investment, thereby providing an a-priori insight into how long it might take to retire an investment loan on the strength of the accrued equity. This type of knowledge is useful for negotiating the terms of acquiring and/or managing large quality-oriented projects, with expected long-term impacts.